THE EFFECT OF PROFITABILITY, LEVERAGE AND LIQUIDITY ON COMPANY VALUE WITH DIVIDEND POLICY AS AN INTERVENING VARIABLE (Empirical Study on Manufacturing Companies in the Consumer Goods Industry Sector Listed on the IDX in 2020-2022) - Muhammad Raghib Ardianto; Wiwik Tiswiyanti; Ratih Kusumastuti (RADJA PUBLIKA, 2025)
This study aims to determine the effect of profitability, leverage and liquidity on company value with dividend policy as an intervening variable (case study of Manufacturing companies in the Consumer Goods Industry Sector listed on the Indonesia Stock Exchange (IDX) for the period 2020-2022). The population in this study were Manufacturing companies in the Consumer Goods Industry Sector for the period 2020-2022. The research sample was selected using a purposive sampling technique, which is a sampling technique using predetermined criteria, so that a total sample of 63 research samples was obtained. This research method uses a quantitative method. This study uses secondary data obtained through data on idx.com, yahoo.finance.com and the respective company websites. The results of the study indicate that profitability and leverage have a positive effect on company value. Profitability, Leverage, Liquidity have no effect on dividend policy. Profitability, Leverage, Liquidity and Dividend Policy have no effect on company value. Dividend Policy is unable to mediate the effect of profitability, leverage and liquidity on company value.